JavaFX programming. Part I - Anderson, Paul.; Safari eBooks ([S.l.] : Addison-Wesley, 2014)
"Oracle is encouraging Java developers to migrate from Swing to JavaFX for GUI development. This video helps developers learn JavaFX and how to apply JavaFX effectively in Java applications. The video is organized into lessons that teach major JavaFX features with separate sublessons that demonstrate how to apply each feature. You'll learn how to draw JavaFX shapes and apply effects to create a richer user experience on the desktop. You'll learn how to use layout managers and GUI controls, including HTML editors and web viewers. You'll learn how to use JavaFX properties and binding expressions to simplify event handling and reduce Java code. You'll also learn how to create animations with JavaFX in this video."--Resource description page.
Title from resource description page (viewed Feb. 19, 2014).
Presenter, Paul Anderson.
Keywords: Java (Computer program language); JavaFX (Electronic resource); Graphical user interfaces (Computer systems); Electronic books